Development of Learning Media to Improve Critical Thinking Skills and Creativity of Vocational Students - Hidayati, Khusnul; Rahmawati, Anis; Wijayanto, Danar Susilo (International Journal of Social Service and Research, 2024)
An important aspect in education is the teacher and the student. Teachers have a duty in teaching and students have obligations in learning. In the learning process, it is necessary to apply the strategies used by the teacher so that students can understand the material presented. One of the strategies used is learning media. Besides, helping in increasing the understanding of students, learning media also helps in improving the critical thinking skills and creativity of vocational students. The purpose of this study is to analyze the development of learning media to improve the critical thinking skills and creativity of vocational students. The research method is qualitative. The data collection technique is carried out by literature study, namely data collection by reviewing books, literature, notes, and various related reports. Then, the data analysis is done by Miles and Huberman analysis, namely data collection, data reduction, data presentation, and conclusions. The results obtained show that the development of learning media is important to improve the critical thinking skills and creativity of vocational students. Simulations, games, and projects are effective solutions for practicing these skills, with simulations providing real experiences, games increasing student interest, and projects allowing students to collaborate on solving complex tasks. Learning media must also be by the interests and needs of vocational students and use relevant technology. Thus, the development of learning media is a critical step in preparing vocational students to face complex future challenges.